Effect of heat-moisture treatment on the physicochemical properties and in vitro digestibility of the starch-guar complex of maize starch with varying amylose content. (October 2018) - Xie, Huifang; Gao, Jingyang; Xiong, Xiaoya; Gao, Qunyu
Abstract: Waxy maize starch (W), normal maize starch (N), and Hylon V (H) were modified by heat-moisture treatment (HMT) with guar gum (G). The physicochemical properties of the HMT starch-guar samples (modified samples: HMT-WG, HMT-NG, and HMT-HG) were investigated and compared with those of starch-guar mixtures (WG, NG, and HG). Then, the swelling power, solubility, granule morphology, thermal properties, in vitro digestibility and isothermal hygroscopic curves of the samples were evaluated. The relative crystallinity of the samples decreased after HMT. HMT-HG tended to form more stable crystals. HG was B + V type, which means that the high amylose starch content results in the formation of a complex with guar gum. In addition, the digestibility of the samples decreased with the decreasing amylose content. HMT-HG showed the highest resistance. Furthermore, HMT decreased the hygroscopicity significantly, decreased the gelatinization enthalpy of the samples in the order of WG > NG > HG and helped slow down the long-term ageing of N/WG. Additionally, HMT-NG was the most resistant to moisture at a lower humidity (45%) and had the lowest gelatinization temperature. Graphical abstract: Scanning electron micrograph of HG and XRD pattern of the samples. Image 1 Highlights: The effect of HMT and amylose content on the starch-Guar mixtures was investigated. HMT decreases the gelatinization enthalpy of the samples in the order of WG > NG > HG. The digestibillity of the samples without HMT decreased with the decrease in amylose content.